Areas of research focus and trends in the research on the application of AIGC in healthcare - Chen Wang; Yingying Zhu; Xuejiao Zhang; Xueqing Chen; Yilin Li; Yongjie Tan; Huiying Qi (Journal of Health, Population and Nutrition)
Abstract Background As a crucial part of current AI technology, the extent of AIGC’s (Artificial Intelligence Generated Content) impact on healthcare, its potential to further drive the development of intelligent healthcare, and its ability to alleviate the current scarcity of medical resources have become highly discussed topics in academia and the healthcare sector. Our aim is to conduct bibliometric study to analyze and visualize the current research hotspots and trends related to the application of AIGC in healthcare. Methods Studies related to the application of AIGC in healthcare that were published from November 30 2022, to December 31 2023, were retrieved via the Web of Science Core Collection. CiteSpace and Microsoft Excel were utilized to analyze and visualize the annual publications, countries, institutions, authors, journals, high cited literature and keywords. Results A total of 3411papers were included, and the number of publications is increasing rapidly in recent two years. The United States and Harvard University are respectively the leading country and institution in terms of the number of research publications on the application of AIGC in healthcare. Thongprayoon Charat and Cheungpasitporn Wisit are outstanding investigators in this field. Nature is the most influential journal in the field of AIGC’ s application in healthcare, whereas Cureus Journal of Medical Science boasts the highest number of publications on this topic. The analysis of keywords and high cited literature has identified current research hotspots, including the impact exploration of the application of AIGC in the healthcare industry, the assessment of applicability, the perception of healthcare related personnel, and the development of AIGC in the healthcare field. Conclusions This paper presents a bibliometric analysis of the research framework and hotspots concerning the application of AIGC in healthcare. The analysis aims to provide a comprehensive understanding of this field for researchers. Future research should focus on establishing regulatory mechanism, optimizing healthcare information services, clarifying the role of AIGC, and continuously developing medical large language models.